1994
DOI: 10.1001/archinte.1994.00420100115015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Repeatedly Reactive HIV-1 EIA and Indeterminate Western Blots

Abstract: Evaluation of persons with reactive HIV-1 enzyme immunoassays and IWB should include an assessment of HIV risk and other possible risk factors, such as alloimmunization (ie, parity or recent immunization) or autoantibodies (ie, antinuclear antibodies and rheumatoid factor). The relationship of IWB among men who reported sex with prostitutes is intriguing and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Two patients with a false-positive MEIA had concomitant infections (an acute cytomegalovirus infection and an amebic liver abscess) that might be the cause of the false-positive results. False-positive enzyme-linked immunosorbent assays have been described before (3,4,6,7), and cross-reactivity is one of the known causes. A false-negative MEIA did not occur.…”
mentioning
confidence: 99%
“…Two patients with a false-positive MEIA had concomitant infections (an acute cytomegalovirus infection and an amebic liver abscess) that might be the cause of the false-positive results. False-positive enzyme-linked immunosorbent assays have been described before (3,4,6,7), and cross-reactivity is one of the known causes. A false-negative MEIA did not occur.…”
mentioning
confidence: 99%
“…One caveat of the Western blot is the occurrence of false negative results, in cases of recent infection or false positive results caused in some cases by the presence of cross-reactive antibodies (29)(30)(31)(32). New immunoblot assays have been developed using recombinant HIV-1/2 proteins and peptides (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…However the one drawback of the WB is the indeterminate result. [1,6,[9][10][11]15,24,[26][27][28] Measures are needed to restrict indeterminate results only to the patients who are in the window period. A large prospective study is needed with application of different kits and a large specimen size may be helpful to choose superior HIV diagnostic aids.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, HIV-2 cross reaction, contaminating cellular antigens on viral lysate based blot strips, infection with human T-cell lymphotrophic virus I/II (HTLV I/II), auto antibodies, pregnancy, abnormal bilirubin levels and in-vitro hemolysis have also been suggested as possible causes of indeterminate WB status. [6][7][8] Previous studies have indicated that approximately 20-30% of HIV-1 ELISA negative and 4-20% of HIV-1 ELISA positive specimens have indeterminate results by WB assay. [9][10][11][12] The problems with indeterminate results are myriad.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation